Exploring ideas generation through a shared artifact: The case of GasTec - Pattinson Steven; Lassalle Paul; Heinonen Jarna; Scott Jonathan M.; Preece David (Sage, 2022)
This case focuses on ideas generation in GasTec, a science-based small business specializing in the design and manufacture of gas sensors and analyzers. The case examines how employees' interaction with a shared boundary object (The "Imagineering Wall") contributed to the generation of innovative new ideas. The case shows how the Wall generated discussion and participation among employees, leading to enhanced absorption of internal and external knowledge. Interacting with the Wall exemplifies how both bottom-up processes through which employees shared knowledge internally, and top-down processes that supported formalized, managerial-led, external collaborations contribute to ideas generation and innovation. The case also highlights the current dilemma of GasTec's Managing Director in deciding whether to continue to support the development of the Wall as part of its innovation strategy.